(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
To achieve optimum yield of onion by placing the seeds at a certain depth in lines, a manually operated drum seeder for onion has been designed, fabricated and tested in Farm Machinery and Postharvest Process (FMP) Engineering Division of Bangladesh Agricultural Research Institute (BARI). The seeder is suitable for the small farmers who have practice of direct seeding of onion under dry land cultivation. The seeder consists of a frame, a PVC drum, furrow openers, furrow closer, wheels and handle. In 2009-2010, the seeder was fabricated in FMP Engineering divisional workshop and tested in experimental plot, BARI, Gazipur. Seed rate of the seeder was 4 kg ha-1 and field capacity was 0.08 ha hr-1. Weight and price of the seeder were 5.5 kg and Tk 2500 per unit, respectively. In 2010-2011, a drug chain was added in the seeder and field performance evaluation of the seeder was repeated comparing with manual line sowing and traditional broadcasting methods in experimental plot of BARI, Gazipur. There was no significant variation between average yield of onion by using the seeder (13.26 ton ha-1) and in that of manual line sowing (12.90 ton ha-1) but there was significantly higher yield of onion by using the seeder than that in traditional (10.25 ton ha-1). But sowing time (6 h ha-1) was significantly lower for seeder use than manual line sowing (48 h ha-1) which contribute to reduce the cost of sowing for direct seeded onion. Int. J. Agril. Res. Innov. & Tech. 3 (1): 26-28, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16051